2015
DOI: 10.4049/jimmunol.1401823
|View full text |Cite
|
Sign up to set email alerts
|

Tick Salivary Sialostatin L Represses the Initiation of Immune Responses by Targeting IRF4-Dependent Transcription in Murine Mast Cells

Abstract: Co-evolution of ticks and the vertebrate immune system has led to the development of immunosuppressive molecules that prevent immediate response of skin-resident immune cells to quickly fend off the parasite. Herein, we demonstrate that the tick-derived immunosuppressor sialostatin L restrains IL-9 production by mast cells while degranulation and IL-6 expression are both unaffected. In addition, the expression of IL-1β and IRF4 is strongly reduced in the presence of sialostatin L. Correspondingly, IRF4- or IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…A follow-up study showed that SialoL also inhibited proliferation of CD4+ T helper cells, dendritic cell (DC) maturation, and the production of proinflammatory cytokines [19]. It was later shown that SialoL diminished interleukin-9 (IL-9) production in Th9 lymphocytes and mast cells [20, 21]. Finally, SialoL impaired production of interferon-β (IFN-β) in DCs activated by Borrelia burgdorferii spirochetes [22].…”
Section: Pluripotency and Redundancy - Some Practical Examplesmentioning
confidence: 99%
“…A follow-up study showed that SialoL also inhibited proliferation of CD4+ T helper cells, dendritic cell (DC) maturation, and the production of proinflammatory cytokines [19]. It was later shown that SialoL diminished interleukin-9 (IL-9) production in Th9 lymphocytes and mast cells [20, 21]. Finally, SialoL impaired production of interferon-β (IFN-β) in DCs activated by Borrelia burgdorferii spirochetes [22].…”
Section: Pluripotency and Redundancy - Some Practical Examplesmentioning
confidence: 99%
“…Inappropriate inflammation is also the cause for several sterile diseases including asthma, inflammatory bowel and autoimmune diseases, chronic inflammation resulting from long-term exposure to irritants, and cancer growth encouraged by immune cell infiltrates [70,7883]. Furthermore, detrimental outcomes can result from an inflammatory response to an injury such as atherosclerosis or a brain aneurysm [84].…”
Section: Resultsmentioning
confidence: 99%
“…The precise inhibition mechanisms by SL and SL2 have not been thoroughly characterized. However, a recent study showed that SL inhibits the production of IL-1β and the transcription factor IRF4 in mast cells, which directly binds the promoter of il-1β [70]. This suggests that SL inhibits pro-inflammatory cytokine production at the RNA level by interfering with transcription factors [70].…”
Section: Tick Saliva Interactions With Tlr and Nlrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tryptogalinin, an I. scapularis salivary Kunitz-type inhibitor, inhibits -tryptase, trypsin, -chymotrypsin, plasmin, matriptase and elastase, showing a potential broad effect against mast cell proteins and other host enzymes (Valdes et al, 2013). Furthermore, I. scapularis sialostatin L affects mast cell activation, resulting in immunosuppression (Klein et al, 2015).…”
Section: Roles Of Peptidase Inhibitors In the Tick−host Interfacementioning
confidence: 99%